Pengaruh Ekstrakurikuler Bahasa Inggris Terhadap Kemampuan Berbahasa Inggris Siswa - Palma Juanta; Cheria Laurence; Meidi Sanjaya; Paula Agusto Jeremy Sihombing; Valerie Alexia (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
English extracurricular activities are one of the school's strategies to improve students' English language skills, especially at the elementary level. This study aims to determine the effect of English extracurricular activities on students' English proficiency improvement. This research employed a quantitative approach using a quasi-experimental method with a one-group pretest-posttest design. The population consisted of all students at SD Cinta Budaya Medan who participated in the English extracurricular program. A purposive sampling technique was used to select 30 active participants. Data were collected through English language proficiency tests administered before and after the extracurricular program and analyzed using the Wilcoxon Signed Rank Test. The findings show a significant improvement in students’ English skills after participating in the program. This study presents a novelty by highlighting the effectiveness of extracurricular activities as a non-formal educational intervention that positively impacts language acquisition. The implication encourages schools to maximize extracurricular programs as an integral part of the learning process outside formal instructional hours.